2016
DOI: 10.5194/acp-16-7569-2016
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of oceanic halocarbons to marine and free tropospheric air over the tropical West Pacific

Abstract: Abstract. Emissions of halogenated very-short-lived substances (VSLSs) from the oceans contribute to the atmospheric halogen budget and affect tropospheric and stratospheric ozone. Here, we investigate the contribution of natural oceanic VSLS emissions to the marine atmospheric boundary layer (MABL) and their transport into the free troposphere (FT) over the tropical West Pacific. The study concentrates on bromoform, dibromomethane and methyl iodide measured on ship and aircraft during the SHIVA (Stratospheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 58 publications
12
44
1
Order By: Relevance
“…The Lagrangian model FLEXPART uses a convection scheme, described and evaluated by Forster et al (2007), to account for vertical transport. Using FLEXPART trajectories with ERA-Interim reanalysis, Fuhlbrügge et al (2016b) were able to simulate VSLS mixing ratios from the surface to the free troposphere up to 11 km above the tropical west Pacific in very good agreement with corresponding aircraft measurements applying a simple source-loss approach. Tegtmeier et al (2013) showed that the FLEXPART distribution of oceanic CH 3 I in the tropics agrees well with adjacent upper tropospheric and lower stratospheric aircraft measurements, thus increasing our confidence in the FLEXPART convection scheme and ERA-Interim velocities.…”
Section: Uncertainties In the Analysismentioning
confidence: 71%
See 3 more Smart Citations
“…The Lagrangian model FLEXPART uses a convection scheme, described and evaluated by Forster et al (2007), to account for vertical transport. Using FLEXPART trajectories with ERA-Interim reanalysis, Fuhlbrügge et al (2016b) were able to simulate VSLS mixing ratios from the surface to the free troposphere up to 11 km above the tropical west Pacific in very good agreement with corresponding aircraft measurements applying a simple source-loss approach. Tegtmeier et al (2013) showed that the FLEXPART distribution of oceanic CH 3 I in the tropics agrees well with adjacent upper tropospheric and lower stratospheric aircraft measurements, thus increasing our confidence in the FLEXPART convection scheme and ERA-Interim velocities.…”
Section: Uncertainties In the Analysismentioning
confidence: 71%
“…The average CHBr 3 emission during the OASIS campaign (910 pmol m −2 h −1 ) was larger than during most campaigns in tropical regions: 1.5 times larger than during TransBrom in the subtropical and tropical west Pacific (Tegtmeier et al, 2012), 1.2 times larger than during DRIVE in the tropical northeast Atlantic (Hepach et al, 2014), and 1.5 times larger than during MSM18/3 in the Atlantic equatorial upwelling (Hepach et al, 2015). Only the SHIVA campaign in the South China and Sulu seas yielded larger CHBr 3 emissions of 1486 pmol m −2 h −1 because of very high oceanic concentrations close to the coast (Fuhlbrügge et al, 2016b). The global open ocean estimate by Quack and Wallace (2003) Average CH 2 Br 2 emissions from the OASIS cruise (930 pmol m −2 h −1 ) are 2-6 times larger than the average cruise emissions listed in Table 3: TransBrom, DRIVE, MSM18/3, SHIVA, and M91.…”
Section: Comparison Of Oasis Vsls Emissions With Other Oceanic Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both could lead to either a shorter or longer residence time of the surface air masses within the MABL or below the trade inversion. However, Fuhlbrügge et al (2016) showed that differences in the MABL height of ERA-Interim and radiosonde observations affect the computed ODR only marginally. Further uncertainties may arise from spatial variations in the VSLS lifetimes and thus the chemical degradation of the compounds we used in this study.…”
Section: Uncertaintiesmentioning
confidence: 99%